Effect of Mineral Acids ( H3PO4 ) on Rooting Response of Fresh Mung Bean ( Phaseolus aureus Roxb.) Cuttings Via Indole Acetic Acid Level - Alwan Al-Delaimy, Abdullah O. (Al-Qadisiyah Journal of Pure Science, 2017)
The influence of H3PO4 as a mineral acid on rooting response of fresh mung bean cuttings has been studied on the level of IAA . The date revealed highly gignificant increase in rooting response of fresh cuttings treated with 0.0001 , 0.001 , 0.01 % concentration of H3PO4 solution , while highly concentrations 0.1 , 0.5% revealed highly significant decrease in rooting response compared to control ( d / H2O ) .Quantitative estimation of IAA by spectrophotometric method verified a highly significant increase of IAA content in hypocotyls of fresh cuttings in optimal concentration of H3PO4